2006
DOI: 10.1021/om050886l
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Cationic Chromium(II) Species in a Catalytic System for Ethylene Tri- and Tetramerization

Abstract: Treatment of the ethylene tetramerization catalyst precursor [PNP]CrCl3 with Me3Al afforded the new divalent catalyst precursor {[PNP]2Cr(m-Cl)AlMe3}[ClAlMe3]0.34[Me4Al]0.66·0.125(hexane)·0.25(toluene) (1). The formation of 1 implies reduction to the divalent state, cationization, and ligand scrambling. The fact that this species displays, upon activation with MAO, a catalytic activity similar to that of the trivalent precursor indicates that reduction of the metal to the divalent state is a step toward the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 34 publications
5
87
0
1
Order By: Relevance
“…They discovered that this unusually high 1-octene selectivity was caused by the unique extended metallacyclic mechanism in operation. 1-Octene was formed by further insertion of ethylene into a seven-membered metallacycloheptane intermediate, whereas 1-hexene was formed by elimination from this species as in other reported trimerization reactions [24,36,[45][46][47].…”
Section: Mechanism Of Ethylene Tetramerizationsupporting
confidence: 53%
“…They discovered that this unusually high 1-octene selectivity was caused by the unique extended metallacyclic mechanism in operation. 1-Octene was formed by further insertion of ethylene into a seven-membered metallacycloheptane intermediate, whereas 1-hexene was formed by elimination from this species as in other reported trimerization reactions [24,36,[45][46][47].…”
Section: Mechanism Of Ethylene Tetramerizationsupporting
confidence: 53%
“…[6] Along the same lines, a comparative testing of two s,p-donating tripyrrolide Cr III and Cr II complexes indicated that the Cr II species was more active while producing an identical product distribution to the Cr III complex. [7] These results led us to believe that Cr III is reduced by the alkyl aluminum activator in the early stages of catalyst formation.…”
mentioning
confidence: 90%
“…Interestingly, in this report combinations of Cr(acac) 3 /PNPNH/AlEt 3 were shown to be completely inactive for catalysis, and as such the authors conclude that the active species most likely contains chloride; a result which is further supported by a subsequent structural study and is analogous to previously reported ethylene trimerisation systems. 33,34,[41][42][43][44] However, while there is no doubt that addition of a chloride source to the reaction mixture yields a positive result, previous reports by Rosenthal and co-workers have also demonstrated that catalytic mixtures containing no chloride can readily give high trimerisation activity and selectivity and as such the exact role of chloro groups in the catalytic mechanism remains unclear. 19,23 At this stage most of the evidence points towards a coordination arrangement such as shown in IV, in which the chloro group attached to aluminium acts as a third weak donor.…”
Section: Introductionmentioning
confidence: 99%